A framework to evaluate the environmental quality and simulate future scenarios of urban forests: Atlantic forest case study - Fengler, Felipe Hashimoto; Moraes, Jener Fernando Leite De; Ribeiro, Admilson Irio [UNESP]; Carvalho, Marcela Merides [UNESP]; Filho, Afonso Peche; Medeiros, Gerson Araujo De [UNESP]; Netto, Roberto Silva; Faria, Lester De Abreu (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The urban growth has several effects in the environment and society. To promote a rational development in cities, the maintenance of green infrastructure is primordial. In this study, we propose a framework to evaluated changes in the environmental quality of forest fragments using open-access satellite data. The environmental quality of forest fragments was obtained using landscape ecology analysis and the prediction of future scenarios by Markov Chain Analysis and Celular Automata. We demonstrate this framework using a location that comprises an environmental preservation area, the JundiaíMirim river basin, containing the remnants of Atlantic forest near the Saõ Paulo state capital, southeast of Brazil. The results showed a constant trend of deterioration in the environmental quality of natural vegetation, attributed to the intense occupation process of urbanization in the watershed. The proposed methodology showed great potential to prevent the deterioration of urban forests, allowing the understanding of driving factors and disturbance dynamic in forest fragments. The locations of very low environmental quality proved to be the most vulnerable to the occupation process, highlighting the need of actions to preserve the Atlantic forest in Jundiaí-Mirim river basin.
Keywords: Markov Chain; Smart ecosystem; Smart environment; Urban forests